RANCANG BANGUN WEBSITE ARSIP AKTIVITAS HARIAN PEGAWAI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN BADUNG - Mahendra, A.A Riky; Anom Cahyadi Putra, I Gst Ngurah (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2019)
The development of information technology has a very rapid impact on the development of human activities, one example is the application of information technology in the form of information systems at the Human Resources Development and Human Resources Agency (BKPSDM) of Badung Regency. This information system helps employees in BKPSDM especially in the data field to help their work. But one of the problems that occurs in BKPSDM in the data field is that employees are still searching for employee map numbers still manually by asking the employee NIP and looking for employee map numbers by looking at the hardcopy that is already in the closet. So that the time needed to find the employee map number is long enough so that the time to do the other tasks is quite drained. From these problems the author makes a solution that is by making an information system that can dance the staff map number by simply entering the NIP on the system named E-Staffing archive. This information system can also import personnel data with the .xlsx file format and export personnel data to file.xls format. This system is built using the CodeIgniter (CI) framework with a PHP backend and MySql database.